Enhanced fluoride removal from drinking water in wide pH range using La/Fe/Al oxides loaded rice straw biochar. Issue 1 (23rd July 2021) - Zhou, Nan; Guo, Xiangxin; Ye, Changqing; Yan, Ling; Gu, Weishi; Wu, Xiangrong; Zhou, Qingwen; Yang, Yuhuan; Wang, Xiaoping; Cheng, Qiwei
Abstract: A novel and highly efficient adsorbent was prepared by loading La/Fe/Al oxides onto rice straw biochar (RSBC), which was tested for the ability to remove fluoride from drinking water. Characterized by SEM, XRD, Zeta potential and FTIR, it was found that the ternary metal oxides were successfully loaded on the surface of biochar in amorphous form, resulting in the formation of hydroxyl active adsorption sites and positive charges, which played a synergistic role in fluoride removal. Through batch adsorption tests, key factors including contact time, initial fluoride concentration, initial pH and co-existing anions effects were investigated. Results showed that the tri-metallic modified biochar (La/Fe/Al-RSBC) had excellent fluoride removal performance with an adsorption capacity of 111.11 mg/g. Solution pH had little impact on the removal of fluoride, the adsorbent retained excellent fluoride removal capacity in a wide pH range of 3.0–11.0. The co-existing anions had almost no effect on the fluoride removal by La/Fe/Al-RSBC. In addition, La/Fe/Al-RSBC could be regenerated and reused. Electrostatic adsorption and ion exchange were responsible for this adsorption behavior. These findings suggested the broad application prospect of a prepared biochar adsorbent based on rare earth and aluminum impregnation for the fluoride removal from drinking water. HIGHLIGHTS: A novel tri-metal oxide loaded rice straw biochar (La/Fe/Al-RSBC) was successfully prepared by simple co-precipitation. La/Fe/Al-RSBC has excellent fluoride adsorption performance with wide pH range. The mechanism of fluoride adsorption involves in electric attraction and ion exchange. Graphical Abstract